Persepsi Masyarakat Terhadap Program Bantuan Langsung Tunai Dana Desa (Blt-Dd) Tahun 2023 Di Desa Sungai Gambir Kabupaten Bungo - Icha Risma Putri,; Nuriah Alfisyahri; Abdul Razak; Irmawati Sagala; Yudi Armansyah; Abdul Malik (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2024)
This research is based on the phenomenon regarding the distribution of BLT assistance in Sungai Gambir Village, Bungo Regency, so it is known that there are various kinds of problems that occur in the community in the process of distributing BLT assistance. This has the impact of community dissatisfaction in receiving direct village cash assistance (BLT-DD) which is not on target. The sample in the study was 90 respondents from a population of 855 Head of the family Sungai Gambir village. The measurement scale uses Likert, and data processing uses SPSS. The results of this research show that the public’s perception of the 2023 BLT-DD Village Fund Direct Cash Assistance Program in Sungai Gambir Village, Bungo Regency, in terms of evaluation and acceptance, can be said to be quite good with a percentage of 69.8%-70%. So the community’s perception is related to the users of BLT funds in 2023 in Sungai Gambir Village, Bungo Regency, where the community perceives that the benefits of the BLT DD program in Sungai Gambir Village, Bungo Regency, are real and these benefits are used to meet their basic needs. They still evaluate this program positively because they understand the criteria for recipients correctly.